Free trade and transnational labour (Abingdon, 2015)
"‘Free trade’ strategies have increasingly become a problem for the international labour movement. While trade unions in the North especially in manufacturing have supported free trade agreements to secure export markets for their companies, trade unions in the Global South oppose these agreements, since they often imply deindustrialisation. Especially the expansion of the free trade agenda into services, public procurement, investment, intellectual property rights as well as investor to state dispute settlement provisions are considered to be problematic.